THE INFLUENCE OF CHURCHES OF THE CITIZENSHIP CATHOLIC PARISHES ON THE LAYOUT AND URBAN SPACE OF MEDIEVAL TOWNS IN THE 13TH AND 14TH CENTURIES - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
One of the most important types of cult buildings in medieval cities were churches for the citizenship Catholic parishes, which began to be built in Italy. In the 12th and 13th centuries on lands of the Baltic Seacoast, the construction of cult buildings expanded with the spread of the Catholic Faith, influencing the spatial organization of the urban environment, and developing church types. Churches for the citizenship Catholic parishes became architectural dominates in cities of the Hanseatic League. Research problem: the development of the planning and structure of churches for the citizenship Catholic parishes changed urban aesthetics; it is necessary to study churches for the citizenship Catholic parishes and layouts of medieval towns organized around the market to preserve historical identity during the development of the contemporary urban environment. Research goal: analysis of the impact of churches for the citizenship Catholic parishes on the layout, visual image and architecturally spatial development of the Hanseatic League cities. Research novelty: analysis of common and local features of churches for the citizenship Catholic parishes and their layout, as well as structural evolution in the Hanseatic League cities during the 13th–14th centuries. Research methods: analysis of archive documents, projects, cartographic materials and studies of published literature, an inspection of churches in nature, and photo fixation.